2022
DOI: 10.1017/qua.2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and chronology of the Cala Mosca site, SW Sardinia (Italy)

Abstract: The relict beach deposit of the Cala Mosca marine terrace is considered an important section of Marine Isotopic Stage (MIS) 5e (ca. 125 ka) sea-level highstands. Analysis of the stratigraphy and sediments of the deposit indicates the presence of a composite marine terrace comprising two superimposed marine units, luminescence dated to the MIS 5e (137 ± 7, 134 ± 7 ka) and MIS 5c (92 ± 6 ka) substages. The stratigraphic superimposition of the two highstands, both placed ~5 m above present sea level, agrees with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
(187 reference statements)
0
1
0
Order By: Relevance
“…So, the architecture of the outcropping deposits can be explained only assuming that the succession developed during a cycle of relative sea-level change. Therefore, the "terraced surface" of previous authors, i.e., the topographic surface topping both the delta and the beach deposits, cannot be attributed to a single episode of relative sea-level stillstand, but it corresponds to the surface of a composite marine terrace sensu [29,30]. Different deposits must be sampled to date the delta top and the beach top.…”
Section: Spineto-bernalda Sectionmentioning
confidence: 97%
See 1 more Smart Citation
“…So, the architecture of the outcropping deposits can be explained only assuming that the succession developed during a cycle of relative sea-level change. Therefore, the "terraced surface" of previous authors, i.e., the topographic surface topping both the delta and the beach deposits, cannot be attributed to a single episode of relative sea-level stillstand, but it corresponds to the surface of a composite marine terrace sensu [29,30]. Different deposits must be sampled to date the delta top and the beach top.…”
Section: Spineto-bernalda Sectionmentioning
confidence: 97%
“…The authors concluded that these terraced marine-deposits record more than a single relative sea-level change in the succession located below each terraced surface, even in the subsurface of the present-day coastal plain; therefore, terraced surfaces topping these deposits could not be genetically linked to the whole succession located below each of these surfaces but, eventually, they could be related to the last of those cycles vertically recorded in the local sedimentary succession [2,4,25,26]. Moreover, the "imbrication" of coastal wedges of different ages, i.e., a series of coastal bodies that cyclically developed one in front of the other at a different time, is worldwide documented and is characterized on top by an apparently single-terraced surface (a composite-terraced surface) [27][28][29][30]. [2] in the vicinity of the area of the present study.…”
Section: Geological Settingmentioning
confidence: 99%
“…Among all dating methods, luminescence dates the last exposition to the sunlight of minerals such as quartz and feldspar before burial and, thus, the deposition time (Lian and Roberts, 2006). The method has been successfully applied to Holocene to Middle Pleistocene Sardinian deposits using quartz and potassium-rich feldspar (K-feldspar) minerals (Casini et al, 2020;Cocco et al, 2019;Pascucci et al, 2014Pascucci et al, , 2022Sechi et al, 2013Sechi et al, , 2018aSechi et al, , 2018bSechi et al, , 2020Sechi et al, , 2023Zucca et al, 2014). Recently, Andreucci et al (2017) successfully applied the luminescence method to date wind blow sediment filling the Bue Marino cave, which is part of a vast karst complex of the Gulf of Orosei.…”
Section: Introductionmentioning
confidence: 99%